Characteristics of Legal Science as Sui Generis - Syadzwina, Dhifa Nadhira; Octavianus, Dwi Caesar; Amrullah, M. Arief; Setyawan, Fendi; Subhan, Ahmad (Nurani, 2023)
Philosophy is a process of reasoning in thinking to make a conclusion to gain knowledge, because humans are thinking creatures, every attitude and action must come from knowledge based on the thinking process. Until now, the position of legal science is still debated because law is perspective and normative, the characteristics of legal science are doubtful in social science or humanities because it has its own characteristics, called sui generis. This research aims to examine the characteristics of legal science as sui generis from the perspective of the philosophy of science. The research method uses normative juridical with secondary data analysis that is related with the problem in a descriptive-qualitative with a philosophy of science perspective. The results showed that the parameters of sui generis can be seen from the perspective of normative science, terminology in a broad and narrow sense, the type and scope of knowledge in normative science and empirical science, also layers of legal science in the form of legal dogmatics, legal theory, and legal philosophy law. Legal science need to understand the history of development of law as the key to identifying sui generis characteristics through analysis of legal theory, legal concepts, and legal principles philosophically in certain conceptual viewpoints as fundamental to legal science, apart from that, legal research is also needed.